The twisted claw - Dixon, Franklin W. (Dixon, Franklin W. Hardy boys mystery stories, 1969)
The Hardy boys embark on another puzzling mystery when they try to discover who is stealing rare collections of ancient pirate treasure and smuggling them out of the United States.